2016
DOI: 10.2502/janip.66.2.2
|View full text |Cite
|
Sign up to set email alerts
|

A complex adaptive system may be essential for cumulative modifications in tool design

Abstract: The cumulative modification of tool designs over time is a crucial development for technological evolution. Cognitive-related prerequisites for this technological capability are innovative behaviour and the faithful inter-generational transmission and maintenance of tool designs by accurate social learning processes. Here, we investigated the hypothesis that a complex of morphological and behavioural adaptations specifically for tool skills is also required. In a novel analysis we compared the tool-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 104 publications
0
19
0
Order By: Relevance
“…Although non-cultural processes are expected to contribute to shaping the technology of New Caledonian crows (Kenward et al 2005;Rutz et al 2018), we should not underestimate the extent to which this was also the case in our tool-making ancestors (e.g., Corbey et al 2016). Therefore, whatever the precise contributions of genetics, individual learning and social transmission (Hunt & Uomini 2016;Rutz et al 2018), the New Caledonian crowand other non-human tool users (e.g., Rutz et al 2016a)provide a powerful comparative framework (Dean et al 2014) for identifying the basic biological processes that enable cumulative technological evolution.…”
Section: Introductionmentioning
confidence: 87%
“…Although non-cultural processes are expected to contribute to shaping the technology of New Caledonian crows (Kenward et al 2005;Rutz et al 2018), we should not underestimate the extent to which this was also the case in our tool-making ancestors (e.g., Corbey et al 2016). Therefore, whatever the precise contributions of genetics, individual learning and social transmission (Hunt & Uomini 2016;Rutz et al 2018), the New Caledonian crowand other non-human tool users (e.g., Rutz et al 2016a)provide a powerful comparative framework (Dean et al 2014) for identifying the basic biological processes that enable cumulative technological evolution.…”
Section: Introductionmentioning
confidence: 87%
“…According to a recent consensus definition (Mesoudi & Thornton 2018), the New Caledonian crow is a compelling candidate for cumulative technological culture (Hunt & Uomini 2016;St Clair et al 2018). A detailed evaluation is beyond the scope of this commentary and will be provided elsewhere, but the key points can be summarised as follows.…”
Section: Introductionmentioning
confidence: 99%
“…These designs vary considerably in shape, size and overall complexity, with striking population differences in tool repertoires [2]. It has been suggested that this diversity results from the cultural accumulation of innovations [2,3]. This is an exciting possibility, given that such cumulative cultural evolution was once believed to be a uniquely human phenomenon [4].…”
mentioning
confidence: 99%
“…Importantly, neither of these studies employed a tool-manufacture paradigm, so they could only make inferences about general, rather than toolmanufacture-specific, social-learning capacities [18]. Given these caveats, it seems premature to rule out the possibility that New Caledonian crows can learn about tool designs from watching -and interacting with -skilled demonstrators [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation